SISTEM INFORMASI PELAYANAN BANK SAMPAH LEBAK INDAH BERBASIS WEBSITE DENGAN MENGGUNAKAN ALGORITMA FIRST IN FIRST OUT (STUDI KASUS BANK SAMPAH DESA LEBAK) - Muhimmatul Mahmuda; Anita Andriani; Reza Augusta Jannatul Firdaus; Ahmad Heru Mujianto (Inovate, 2025)
The lebak Indah waste bank server information system has several activities, including customer service, customer registration, queues as well as depositing and withdrawing balances. The purpose of creating a waste bank service information system is to help the performance of officers and customer queues at the beautiful waste bank. Queue can be interpreted as steps starting from the moment the customer arrives, waiting for service, and getting service. An unstructured queue system can interfere with the service well. However, together because of the current development of information technology, there have been many developments in the queue system. The purpose of this research is to design and develop data systems. Web-based beautiful lebak waste bank service with case studies found in Lebak Village garbage bank. The garbage bank service is on the object sometimes causing long and irregular queues, especially when the time of weighing waste causes customers to be crammed to queue. Based on the description of the problem, researchers are interested in developing and building a Web-Based Lebak Indah Waste Bank Service Information System with the Help of FIFO Algorithm (Case Study of Lebak Village Waste Bank). FIFO is a method to solve queue problems that may be applied as the first way to enter is considered as the first way to exit. Keywords: Information System, Service, Queue, Website, First In First Out